Constructing the teaching process from inside out: how preservice teachers make sense of their perceptions of the teaching of the 4 skills - Silva, Marimar da (2003)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.